Constitution of the systems {V, Nb, Ta}-Sb and physical properties of di-antimonides {V, Nb, Ta}Sb2. (October 2015) - Failamani, F.; Broz, P.; Macciò, D.; Puchegger, S.; Müller, H.; Salamakha, L.; Michor, H.; Grytsiv, A.; Saccone, A.; Bauer, E.; Giester, G.; Rogl, P.
Abstract: The binary phase diagrams {V, Nb, Ta}-Sb below 1450 °C were studied by means of XRPD, EPMA, and DTA measurements. In the V-Sb system, five stable binary phases were observed in this investigation: V3+x Sb1−x, ℓT-V3 Sb2, hT-V2−x Sb, V7.46 Sb9, V1−x Sb2 . The V-Sb phase diagram is characterized by two degenerate eutectic reactions: L↔V3+x Sb1−x +(V) (T > 1450  °C at 18.1 at.% Sb) and L↔V1−x Sb2 +(Sb) (T=(621 ± 5)°C at ∼99 at.% Sb), three peritectic reactions: L + V3+x Sb1−x ↔hT-V2−x Sb (T=(1230 ± 10)°C at ∼42 at.% Sb), L + hT-V2−x Sb↔V7.46 Sb9 (T=(920 ± 10)°C at ∼87 at.% Sb), and L + V7.46 Sb9 ↔V1−x Sb2 (T=(869 ± 5)°C at ∼88 at.% Sb), a peritectoid reaction: V3+x Sb1−x  + hT-V2−x Sb↔ℓT-V3 Sb2 at (875 ± 25)°C, a eutectoid reaction: hT-V2−x Sb↔ℓT-V3 Sb2 +V7.46 Sb9 at (815 ± 15)°C and congruent melting of V3+x Sb1−x (T > 1450 °C). An X-ray single crystal study of V5 Sb4 C1−x proved the existence of interstitial elements in the octahedral voids of a partially filled Ti5 Te4 -type structure (x∼0.5; RF2  = 0.0101), therefore this phase (earlier labeled "V5 Sb4 ") was excluded from the binary equilibrium phase diagram. V5 Sb4 C1−x is the first representative of a filled Ti5 Te4 -type structure. A re-investigation of the Nb-Sb system removed the contradiction between the hitherto reported phase diagrams and confirmed the version derived by Melnyk et al. (see ref. [1]). Three binary phases exist in the Ta-Sb system: Ta3+x Sb1−x, Ta5 Sb4, TaSb2 . Due to instrumental limits (≤1450 °C), only the peritectic reaction of TaSb2 : L + Ta5 Sb4 ↔ TaSb2 ((1080 ± 10)°C at ∼92 at.% Sb) and a degenerate Sb-rich eutectic reaction (L↔TaSb2 +(Sb); (622 ± 5)°C; ∼99 at.% Sb) have been determined. Physical properties (mechanical and transport properties) of binary di-antimonides were investigated with respect to a potential use of these metals either as diffusion barriers or electrodes for thermoelectric devices based on skutterudites. All group-V metal di-antimonides have low metallic-type resistivity and relatively high thermal conductivity. Magnetic field has little influence on the resistivity of V1−x Sb2 at low temperature, while on {Nb, Ta}Sb2 it increases the resistivity, especially on NbSb2 . The coefficient of thermal expansion (CTE) decreases from V1−x Sb2 to TaSb2, particularly the CTE value of NbSb2 is in the range of average n-type filled skutterudites. In contrast to the CTE value, elastic moduli increase from V1−x Sb2 to TaSb2 . The value for V1−x Sb2 is in the range of Sb-based skutterudites, whereas the values for {Nb, Ta}Sb2 are significantly higher. Graphical abstract: Highlights: Binary phase diagrams {V, Ta}-Sb (<1450 °C) are established for the first time. Our re-investigation of the Nb-Sb system confirmed the version reported by Melnyk et al. V5 Sb4 C1−x is the first representative of the filled-Ti5 Te4 -type structure. Transport and mechanical properties are reported for {V, Nb, Ta}Sb2 .